The Application of Experimental Methods to Improve the Learning Outcomes of High School Students on Colloid Material - Gani, Abdul; Wati, Armida; Winarni, Sri; Syahrial, Syahrial; Nasir, Muhammad (UIN Fatmawati Sukarno Bengkulu, 2025)
The low ability of students to achieve learning outcomes in chemistry concepts, including colloid material, is influenced by various factors such as limited study time, inadequate facilities, and teaching methods that do not align with the material. One effective method for enhancing student learning outcomes is the experimental method. This study aims to assess student activity, learning results, and feedback on the learning process for colloids. Utilizing a descriptive qualitative approach, the research involved 22 students from class XI MIA 2 at SMA Negeri 1 Terangun, selected through purposive sampling. Instruments included observation questionnaires, learning outcome tests, and student feedback questionnaires. Content validation has been conducted for all instruments by one expert and one practitioner, who have declared them valid and feasible to use. Results showed increased student activity with 94% at the second meeting and 96% at the third. Learning outcomes improved, with average completion rates rising from 64% at the second meeting to 86% at the third. Feedback indicated 61% strongly agree, 36% agree, and 3% somewhat agree regarding the experimental method. This study concludes that the experimental method for exploring the types and properties of colloids can enhance student activity and learning outcomes.